Análise sensorial de cervejas elaboradas com mel - Brunelli, Luciana Trevisan [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Universidade Tecnologica Federal do Parana (UTFPR), 2014)
The aim of this study was produce and analyze through sensory analysis beer made with honey as malt adjunct. Treatments were based in a 3x3 factorial derived from the combination of three concentrations of original extract (11, 13 and 15°Brix) and three percentages of honey in the wort (0, 20 and 40%). The mashing process was conducted by the infusion process, and then added honey during the boiling step. After clarified, the extract contests of the wort was adjusted and bottom-fermenting yeast was inoculated in that. Fermentation occurred at 10°C. Beer was manually bottled and stored in a freezer at the temperature of 0°C for 15 days for their maturation. The sensory analysis was accomplished through the test of structured hedonic scale of nine points. The sensory attributes analyzed were appearance, aroma, flavor and global evaluation. The results for each attribute, were subjected to variance analysis for completely randomized experiment. All beers elaborate were approved by the team sensory, and the presence of honey in the formulation of common beers (11°Brix) and extra (13°Brix) did not affect the acceptance of tasters for all sensory attributes evaluated. However, the strong beers with honey in its composition had higher acceptance of tasters.

O objetivo deste trabalho foi produzir e analisar sensorialmente cervejas utilizando mel como adjunto de malte. Os tratamentos originaram-se de um fatorial 3x3 proveniente da combinação de três concentrações de extrato primitivo (11, 13 e 15°Brix) e três porcentagens de mel na formulação do mosto (0 20 e 40%). A mosturação foi realizada pelo processo de infusão, sendo o mel adicionado na etapa de fervura. Depois de clarificado, o mosto teve seu teor de extrato corrigido e foi inoculado com levedura de baixa fermentação. A fermentação ocorreu a 10°C. A cerveja foi engarrafada manualmente e armazenada em freezer à temperatura de 0°C por 15 dias, para a sua maturação. A análise sensorial foi realizada por meio do teste de escala hedônica estruturada de nove pontos. Os atributos sensoriais analisados foram aparência, aroma, sabor e avaliação global. Os resultados obtidos, para cada atributo, foram submetidos à análise de variância para experimento inteiramente casualizado. Todas as cervejas elaboradas foram aprovadas pela equipe sensorial, sendo que a presença de mel na formulação das cervejas comuns (11°Brix) e extra (13°Brix) não interferiu na aceitação dos provadores para todos os atributos sensoriais avaliados. Entretanto, as cervejas fortes com mel em sua composição obtiveram maior aceitação dos provadores.
Sensory analysis of beer produced with honey
Keywords: Alcoholic beverage; Hedonic scale; Acceptance testing; Bebida alcoólica; Escala hedônica; Teste de aceitação